7(1+r)=-2-2(2-4r)

Simple and best practice solution for 7(1+r)=-2-2(2-4r) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(1+r)=-2-2(2-4r) equation:


7(1+r)=-2-2(2-4r)

We simplify the equation to the form, which is simple to understand
7(1+r)=-2-2(2-4r)

Reorder the terms in parentheses
+(+7+7r)=-2-2*(2-4r)

Remove unnecessary parentheses
+7+7r=-2-2+*(+2-4r+)

Reorder the terms in parentheses
+7+7r=-2+(-4+8r)

Remove unnecessary parentheses
+7+7r=-2-4+8r

We move all terms containing r to the left and all other terms to the right.
+7r-8r=-2-4-7

We simplify left and right side of the equation.
-1r=-13

We divide both sides of the equation by -1 to get r.
r=13

See similar equations:

| s=-16*t^2+16*t+12 | | -2x=x-15 | | (-13/2)*(8/3) | | 3x+5=+10 | | 6x/12-7x/20=0 | | 8x^2-7x+5-4x-11x^2= | | 4.5=3.4+m | | 5x+12=7x-2 | | -2x+8-3x=7 | | 2x+4-7x=-21 | | (x-1)(2x+5)+(x-1)2=0 | | -4x=2x+18 | | 6x^12-7x^20=o | | 3x-37=7x-1 | | 15x=6x+36 | | r-0.4=-7.1 | | 7x+3-4x=17 | | s=-16t^2+16t+12 | | y/4=16 | | 12x-(-8x)(2)= | | -389(-216)= | | (1+x)(2x+7)=0 | | -5-3x+2=-8x+3-3x | | -5-3x+2=-8+3-3x | | 11x+4-2x=3x-9 | | 6v^2-24v=0 | | -4+y+7=5y+23 | | y-14=5 | | -1*(x+4)=3*(x+5) | | 4x+17=5x+10 | | m/2=8 | | 6y=2y+4 |

Equations solver categories